2016
DOI: 10.1186/s13104-015-1797-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular forensics in avian conservation: a DNA-based approach for identifying mammalian predators of ground-nesting birds and eggs

Abstract: BackgroundThe greater sage-grouse (Centrocercus urophasianus) is a ground-nesting bird from the Northern Rocky Mountains and a species at risk of extinction in in multiple U.S. states and Canada. Herein we report results from a proof of concept that mitochondrial and nuclear DNAs from mammalian predator saliva could be non-invasively collected from depredated greater sage-grouse eggshells and carcasses and used for predator species identification. Molecular forensic approaches have been applied to identify pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Similarly, treenesting birds like the endangered 'elepaio (Chasiempis sandwichensis ibidis) are depredated by invasive rats in Hawaii, as evidenced by trail cameras (VanderWerf 2001). Environmental DNA provides another tool for identifying nest predators, which in some cases may be more applicable to certain field situations than other methods (Hopken et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, treenesting birds like the endangered 'elepaio (Chasiempis sandwichensis ibidis) are depredated by invasive rats in Hawaii, as evidenced by trail cameras (VanderWerf 2001). Environmental DNA provides another tool for identifying nest predators, which in some cases may be more applicable to certain field situations than other methods (Hopken et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental DNA can be used to identify the predators of depredated bird eggs or carcasses by swabbing saliva from the eggs or carcasses. This technique has proven successful in determining the predators of greater sage grouse (Centrocercus urophasianus) nests: Hopken et al (2016) used two mitochondrial loci to screen for predator DNA from swabs taken from grouse eggs and carcasses (see case studies below for more details).…”
Section: Edna -Specifications and Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study was even able to obtain red fox ( Vulpes vulpes ) or dog saliva from eggshells, successfully identifying the predator in one‐third of the egg samples tested (Dawson et al ). A sage grouse ( Centrocercus urophasianus ) predation study, which identified canid predators to at least family level, actually had greater amplification success from eggshells than from adult carcasses (Hopken et al ).…”
mentioning
confidence: 99%